The Dimensionality of Signs, Tools, and Models An Introduction - Bunn, James H. (Indiana University Press, 1981)
Semiotics, the study of the function of signs, can seem bewildering to the uninitiated. James H. Bunn's dimensional approach makes semiotics accessible as no previous work has succeeded in doing. The book is organized to correspond with the several Euclidean dimensions: it explores three-dimensional instruments as they exist "in the round"; the relationship between pictorial images and a two- dimensional plane, as in maps and paintings; abstract signs, such as mathematical figures and musical notes that are strung together in one-dimensional series; and spatio-temporal (four-dimensional) models that are equated with whole systems. Bunn roams freely in a variety of fields-literature, history, mythology, anthropology, technology. The Dimensionality of Signs, Tools, and Models is a stimulating guide for the general reader, and an important breakthrough for those special readers interested in the philosophy of communication.